Code-Switching Practices among English Teacher in Early Childhood in Bilingual Education - Ratih Sulistiya Ningsih; Gatot Sutapa; Regina Regina; Endang Susilawati (FOSTER: Journal of English Language Teaching, 2026)
This study aims describe how English teacher use code-switching practices in the classroom. The participants of this study are four teachers with experience teaching in kindergarten in Pontianak. This study was qualitative approach through case study. The data were collected by in-depth interviews. The result of this study that teachers used three types of code-switching: tag-switching, inter-sentential switching, and intra-sentential switching. These strategies were primarily employed to clarify instructions, manage classroom behavior, build rapport, and adapt to students’ varying levels of English proficiency. The frequency and manner of code-switching were also influenced by the children’s age group and the teachers’ years of teaching experience. Teachers of younger learners tended to switch languages more frequently to ensure comprehension, while more experienced teachers applied code-switching more selectively and strategically. This study concludes that code-switching should not be viewed as a sign of linguistic deficiency but rather as a responsive and effective pedagogical tool. Further research is recommended to examine the long-term impact of code-switching on bilingual development and to investigate its implementation in broader educational contexts.